Prevalence of nursing diagnoses of breastfeeding in the mother-infant dyad in basic health unit - Ocilia Maria Costa Carvalho; Karolina Rodrigues Silva; Lívia Zulmyra Cintra Andrade; Viviane Martins da Silva; Marcos Venícios de Oliveira Lopes (Universidade Federal do Ceará, 2014)
A cross-sectional study conducted with 28 mother-infant dyads, users of a Family Health Center of Fortaleza-CE, Brazil, that aimed to identify the nursing diagnoses of breastfeeding, their frequency of occurrence, defining characteristics, and the value of maternal confidence based on the breastfeeding self-efficacy scale. Data collection happened during September and October 2010, using interviews, anamnesis, and physical examination of the dyad. The most prevalent diagnosis was Effective breastfeeding (50%). The breastfeeding self-efficacy scale revealed significance in the presence of the nursing diagnoses Effective breastfeeding and the absence of Interrupted breastfeeding. Although the diagnosis Effective breastfeeding presented a significant occurrence, we verified the need for effective actions of nurses in the breastfeeding process.